2018
DOI: 10.1128/aem.02773-17
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Function and Global Distribution of Polyethylene Terephthalate (PET)-Degrading Bacteria and Enzymes in Marine and Terrestrial Metagenomes

Abstract: Polyethylene terephthalate (PET) is one of the most important synthetic polymers used today. Unfortunately, the polymers accumulate in nature and to date no highly active enzymes are known that can degrade it at high velocity. Enzymes involved in PET degradation are mainly α- and β-hydrolases, like cutinases and related enzymes (EC 3.1.1). Currently, only a small number of such enzymes are well characterized. In this work, a search algorithm was developed that identified 504 possible PET hydrolase candidate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
288
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 303 publications
(322 citation statements)
references
References 44 publications
7
288
0
2
Order By: Relevance
“…For PET, the abundance of polyester hydrolases in the environment was investigated in detail. The results suggest that this enzyme activity is rather rare, but more frequent in crude oil rich environments 26,59,60 . Currently further metagenome and mechanistic studies of this important enzyme class are carried out by the scientific community, most likely discovering protein family members with superb activities or at least interesting amino acid variations.…”
Section: Discussionmentioning
confidence: 87%
“…For PET, the abundance of polyester hydrolases in the environment was investigated in detail. The results suggest that this enzyme activity is rather rare, but more frequent in crude oil rich environments 26,59,60 . Currently further metagenome and mechanistic studies of this important enzyme class are carried out by the scientific community, most likely discovering protein family members with superb activities or at least interesting amino acid variations.…”
Section: Discussionmentioning
confidence: 87%
“…For PET degradation, comprehensive activitybased screening studies are missing. However, a bioinformatics study using a hidden Markov model succeeded to identify PET hydrolase genes using the UniProtKB database and more than 100 metagenome datasets, many of which originated from marine sources (Danso et al, 2018). The reported frequency of PET hydrolases was, dependent on the origin of the metagenomic sample, between 0.0001 and 1.5 hits per megabases of sequence, with the highest hit rate in a metagenome obtained from an oil polluted environment (Danso et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, a bioinformatics study using a hidden Markov model succeeded to identify PET hydrolase genes using the UniProtKB database and more than 100 metagenome datasets, many of which originated from marine sources (Danso et al, 2018). The reported frequency of PET hydrolases was, dependent on the origin of the metagenomic sample, between 0.0001 and 1.5 hits per megabases of sequence, with the highest hit rate in a metagenome obtained from an oil polluted environment (Danso et al, 2018). In contrast to the marine origin of many predicted PET hydrolases, most of the PET degrading enzymes studied so far originate from terrestrial sources, with Cut190 from Saccharomonospora viridis (Kawai et al, 2014), Tha_Cut1 from Thermobifida alba (Ribitsch et al, 2012), Thc_Cut1 and Thc_Cut2 from T. cellulosilytica (Ribitsch et al, 2012), Tfu_0883, Tfu_0882 and TfCut2 from T. fusca (Chen et al, 2010;Roth et al, 2014) and LCC identified from a leafbranch compost metagenome (Sulaiman et al, 2012) for example.…”
Section: Introductionmentioning
confidence: 99%
“…a more accessible active site) display the highest activity against PET [34]. A recent bioinformatic analysis has investigated the distribution of genes encoding for homologs of these esterases in terrestrial and marine metagenomes and has allowed to identify 504 new hydrolases [35]. The two main conclusions of this study are: i) genes potentially encoding polyester hydrolases are rare, and ii) their taxonomic distribution seems to be related to the niche studied, with Actinobacteria or Proteobacteria being more prominent hosts in terrestrial environments whereas Bacteroidetes are the most frequent hosts in marine metagenomes [35].…”
Section: 1enzymatic Hydrolysis Of Petmentioning
confidence: 99%